THE INFLUENCE OF WEBSITE QUALITY, PERCEIVED BENEFITS, E-WOM, SECURITY TOWARDS ONLINE REPURCHASE INTEREST WITH TRUST AS THE MEDIATING VARIABLE - Jennifer Katherine Tanjung; Rubiyatno; Lucia Kurniawati (MANAJEMEN DEWANTARA, 2022)
This study aims to find out whether: 1) trust mediates the influence of website quality toward repurchase interest, 2) trust mediates the influence of the perceived benefits toward repurchase interest, 3) trust mediates E-WOM's influence toward repurchase interest, 4) trust mediates security influence toward repurchase interest, in Lazada consumers in Yogyakarta. The population in this study are the locals of Yogyakarta community who had made an online purchase at Lazada. The sampling technique used purposive sampling, data was obtained by distributing online questionnaires by using google form to 116 respondents. The data analysis technique in this study is Partial Least Square using the WarpPLS 6.0 application. The results showed that: 1) trust mediated the influence of website quality toward repurchase interest, 2) trust mediated the influence of perceived benefits toward repurchase interest, 3) trust mediated E-WOM influence toward repurchase interest, 4) trust does not mediate the influence of security toward repurchase interest